A systematic review on the significance of reflective teaching in teaching performance - Ana Elvia Jakfar; Refanja Rahmatillah (Universitas Merdeka Malang, 2023)
Reflective teaching is vital for improving teaching performance. Self-reflection has been expected to bring a positive impact on reflective teaching. Hence, this study explores the significance of reflective teaching with two research questions: 1) How is reflective teaching through self-reflection seen? 2) What are the best strategies for implementingreflective teaching? The study was conducted with a qualitative approach through systematic review by analyzing some studies related to the research variables. Previous studies on the research questions were formulated, followed by analyzing and synthesizing the data. The result of the study indicates that the importance of journaling or keeping a diary for teachers as a means of self-reflection is still relevant today and still plays a role in teaching reflection. However, teaching reflection alone does not completely assist teachers in receiving thorough and beneficial reflection to enhance their teaching performance. Other important strategies such as peer observation, reflection training, peer observation, and the use of students such as students' assessment and results also carry out important parts in reflective teaching.